Peran Environmental, Social and Governance dalam Memenuhi Prinsip Good Corporate Governance Melalui Transformasi Digital Pada Perusahaan Pertambangan Yang Terdaftar di Bursa Efek Indonesia - Tsaltsa Puspita Sari; Vika Fitranita (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the effect of Environmental, Social and Governance (ESG) on the fulfillment of Good Corporate Governance (GCG) principles with Digital Transformation as a moderating variable in mining companies listed on the Indonesia Stock Exchange. This study employs a quantitative research method with a descriptive approach. The research sample consists of 26 mining companies selected through purposive sampling during the 2021–2023 period, resulting in 78 observations. Data were obtained from the companies' annual reports and sustainability reports. The data analysis techniques used include descriptive statistical analysis, classical assumption tests, simple linear regression, and Moderated Regression Analysis (MRA). The results indicate that ESG has a positive and significant effect on GCG principles, as evidenced by a t-value of 5.243 > t-table of 1.662 with a significance value of 0.000. This suggests that the higher the company's commitment to implementing ESG values, the better the company's ability to fulfill good corporate governance principles. However, the interaction test results reveal that Digital Transformation is unable to moderate the relationship between ESG and GCG principles, with an interaction variable significance value of 0.272 > 0.05. This condition indicates that digital transformation in Indonesian mining companies has not been fully integrated with ESG implementation in supporting the improvement of corporate governance quality.